A Flexible Electromagnetic Interference Shielding Fabric Prepared by Construction of PANI/MXene Conductive Network via Layer‐by‐Layer Assembly. Issue 6 (27th January 2021) - Yin, Guang; Wang, Yu; Wang, Wei; Qu, Zhongji; Yu, Dan
Abstract: The electromagnetic interference (EMI) shielding textiles accomplishing high‐level EMI protective performance and wear comfort has been designed and developed. 1D polyaniline nanowires and 2D transition metal carbide/carbonitride nanosheets are loaded on the carbon fiber fabric via a layer‐by‐layer (L‐b‐L) assembly approach to fabricate a functional layer and followed with a polydimethylsiloxane (PDMS) coating. The resultant fabric exhibits a high electrical conductivity of ≈325 S m −1 and the EMI shielding effectiveness ≈35.3 dB with only 0.376 mm thickness. Benefiting from the hydrophobic effect of thin PDMS film, a satisfactory self‐cleaning performance with a large contact angle of 135.2° is achieved. Furthermore, favorable flexibility, air permeability (346 mm s −1 ), and thermal management further broaden the field of practical application. This work can provide a new solution for next‐generation EMI shielding materials in view of the comprehensive performance. Abstract : An organic/inorganic conductive network, consisting of 1D polyaniline nanowires and 2D transition metal carbide/carbonitride nanosheets, is constructed on the carbon fiber fabric via a layer‐by‐layer assembly approach and followed with a polydimethylsiloxane coating. This work can provide a new solution for next‐generation electromagnetic interference shielding materials in view of the comprehensive performance.